2020
DOI: 10.3892/etm.2020.9476
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum IgG subclasses in patients with liver disease: A retrospective study

Abstract: Viral and alcoholic liver disease, drug induced liver disease (DILD), primary biliary cirrhosis (PBC) and autoimmune hepatitis (AIH) are among the most common liver diseases observed in clinical practice. These diseases lack unique clinical characteristics at the beginning of pathogenesis, which renders specific diagnosis difficult. Immunoglobulin G (IgG) subclasses are the main isoform of antibodies that can be found in the serum that serve important protective roles in immunity. The present study aimed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Serum IgG4 was often used to exclude IgG4‐related diseases. Zheng W's study indicated that certain serum IgG subclass levels were selectively increased or decreased depending of the type of liver disease, and IgG1/IgG level ratios in patients with viral liver disease were significantly increased 26 . Thus, compared with IgG2, IgG3 and IgG4, more attention should be paid to IgG1 in CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IgG4 was often used to exclude IgG4‐related diseases. Zheng W's study indicated that certain serum IgG subclass levels were selectively increased or decreased depending of the type of liver disease, and IgG1/IgG level ratios in patients with viral liver disease were significantly increased 26 . Thus, compared with IgG2, IgG3 and IgG4, more attention should be paid to IgG1 in CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to a subclass switch from IgG3 to the other three IgG subclasses, in the course of which the disease becomes more chronic, and we speculate that this might be related to the long hinge of IgG3. Serum IgG3 was also found to be significantly increased in primary biliary cirrhosis, this liver disease being another autoimmune disorder (38)(39)(40).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 92%
“…In other autoimmune diseases, such as systemic lupus erythematosus, differential expression/elevation of IgG subclasses have been reported with significantly higher levels of IgG1, IgG2, and IgG3 compared to healthy controls, but no correlation has been shown between IgG subclasses and distinct clinical features [ 7 ]. IgGs are the main isoform of antibodies that can be found in the serum and that serve important protective roles in immunity [ 8 ]. The present study aimed to investigate serum IgG subclass distribution in patients with PSC and its possible association with PSC outcomes.…”
Section: Introductionmentioning
confidence: 99%